Fault detection and assessment in an AC microgrid system using modified complex plane via positive sequence current measurement - Chinmayee Biswal; Pravat Kumar Rout; Binod Kumar Sahu; Manohar Mishra (Results in Engineering)
Integrating distributed generations (DGs) into microgrids leads to many significant issues and challenges in fault detection due to bidirectional power flow, inertia change, fault current variation under different operating conditions, and topological changes. To bring an optimal solution to fault detection, this article introduces a novel protection scheme utilizing a modified complex plane or α-plane strategy based on positive sequence current. The proposed approach leverages the magnitude and phase angle of the modified current ratio (MCR), specifically utilizing the complex signal retrieved from the positive sequence current at both ends of the distribution line. Under normal operating conditions the MCR lies within the dead zone and for external faults, the MCR remains within a restraining region. On the other hand, during internal faults, the MCR shifts inside the operating area. The proposed technique undergoes a wide range of evaluation across various types of faults, including high-resistance faults (HRFs), fault location variation, current transformer (CT) saturation, DG penetration, and sampling frequency fluctuations, especially in grid-connected (GC) modes of operation. Additionally, several non-fault circumstances are analyzed to confirm the method's effectiveness. The advantages of the proposed schemes are demonstrated through a comparative analysis with those of existing schemes. Extensive testing is conducted on a 9-bus CERTS AC distribution system incorporating three DGs. Furthermore, the proposed α-plane based protection approach is validated using the IEEE-34 Bus test system in MATLAB/SIMULINK platform.